Bacterial isolates in urinary tract infection among pregnant women - Lingala, Shilpa; Babu, Suresh (Asian Journal of Medical Research, 2012)
Background: To assess bacterial isolates in urinary tract infection among pregnant women. Methodology: One hundred ten antenatal women between 12-16 weeks of gestation were selected. A clean catch mid-stream urine specimen was collected. Colony count of 100 or more equals to ? 105 CFU/ml & considered as significant bacteriuria. Results: Age group 18- 22 years comprised of 55 patients, 22- 26 years had 35, 26- 30 years had 20 and 30- 34 years had 5 patients. The difference was significant (P<0.05). Asymptomatic bacteriuria (ABU) was seen in 30 and asymptomatic bacteriuria (ABU) in 42 patients. The prevalence found to be 65.4%. The difference was significant (P< 0.05). In ABU and in patients with symptomatic bacteriuria, bacteria isolates were streptococcus Spp. in 20% and 25%, Pseudomonas Spp. in 14% and 5%, Acinetobactor Spp. in 6% and 2%, Staph. Aureus in 28% and 33% and E. coli in 32% and 35% respectively. The difference was significant (P< 0.05). Conclusion: Common isolates seen in pregnant women were E. coli, staph. aureus, Streptococcus spp., pseudomonas spp., candida spp. and acinobacter spp.